Ethics in rehabilitation : a clinical perspective - Kornblau, Barbara L; Kornblau, Barbara L; Burkhardt, Ann (Thorofare, NJ : SLACK, 2012)
Ethical decision-making is a critical component in the broad spectrum of rehabilitation and health care professions today. Ethics in Rehabilitation: A Clinical Perspective, Second Edition was developed to give health and rehabilitation professionals the knowledge and tools they need to approach and solve the ethical dilemmas that challenge them in everyday practice.
Ethics : the basics -- Legal issues in ethical decision making -- Ethics and the heath care system -- Ethics and research in health and rehabilitation -- Ethics and the law : the interface -- Analyzing ethical dilemmas -- Avoiding ethical and legal dilemmas
Includes bibliographical references and index
Keywords: Medical rehabilitation -- Moral and ethical aspects; Rehabilitation -- Law and legislation -- United States; Rehabilitation -- ethics; Ethics, Clinical; Rehabilitation -- legislation & jurisprudence; United States